2022
DOI: 10.1515/ntrev-2022-0035
|View full text |Cite
|
Sign up to set email alerts
|

Advances in ZnO: Manipulation of defects for enhancing their technological potentials

Abstract: This review attempts to compile the physics and chemistry of defects in zinc oxide (ZnO), at both, the fundamental and application levels. The defects, either inherent ones or introduced externally, have broadened the ZnO material field in various directions. The ZnO material exhibits many defect-attributed properties leading to broad technological applications: electronic and optoelectronic devices, sensors, optical components, ceramic industry, biomedical, catalysis, lightening, etc. Considering the huge def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 425 publications
1
39
0
Order By: Relevance
“…Due to its physicochemical property and porous structure, DE has efficient adsorbent properties, and it has been observed that it may effectively reduce the fishy odor during low-temperature adsorption. In addition, ZnO may dissociate hydrogen in a heterogeneous manner, and a ZnO-tailored matrix would increase the number of positively charged volatile molecules with high adsorbent material potential [ 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to its physicochemical property and porous structure, DE has efficient adsorbent properties, and it has been observed that it may effectively reduce the fishy odor during low-temperature adsorption. In addition, ZnO may dissociate hydrogen in a heterogeneous manner, and a ZnO-tailored matrix would increase the number of positively charged volatile molecules with high adsorbent material potential [ 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 37 , 38 , 39 , 40 ] The formation of ZnO NPs by this approach is highly appealing as ZnO NPs present wide technological applications due to their unique properties. These include electro‐optical properties, [ 41 , 42 ] which can be used in devices such as ultraviolet (UV) light‐emitting diodes (LEDs), [ 42 , 43 ] blue luminescent devices or UV lasers [ 44 ] ; photo(electro)catalytic water treatment, [ 45 , 46 , 47 ] antibacterial agents, [ 48 , 49 ] solar cells, [ 50 , 51 , 52 , 53 , 54 ] and others. [ 55 , 56 ] Such unique properties require not only the ZnO material to be nanosized, but also to be homogeneously dispersed without agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…Insoluble forms of zinc are mostly ZnO, Zn 3 (PO 4 ) 2 , ZnCO 3 , and metallic Zn. The usable form of zinc by the plant is divalent cations (Ayoub et al, 2022 ). Zinc-solubilizing fertilizers contain the zinc solubilization bacteria which produce the organic acids to solubilize the insoluble zinc to Zn +2 , thereby enhancing zinc uptake in plants (Nitu et al, 2020 ).…”
Section: Types Of Biofertilizers and Their Role In Crop Production An...mentioning
confidence: 99%